2021
DOI: 10.1007/s11883-021-00955-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in the Management of Dyslipidemia: Which, When, and for Whom? Could Nutraceuticals Help Low-Risk Individuals with Non-optimal Lipid Levels?

Abstract: Purpose of Review The aim of this review is to summarize the available clinical efficacy and safety data related to the most studied and used lipid-lowering nutraceuticals. Recent Findings A growing number of meta-analyses of randomized clinical trials supports the effectiveness and tolerability of some lipid-lowering nutraceuticals such as red yeast rice, plant sterols and stanols, soluble fibers, berberine, artichoke extracts, bergamot polyphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 107 publications
3
50
0
Order By: Relevance
“…Systematic reviews showed that berberine improved obesity parameters including BMI [ 68 , 69 ]. Meanwhile, a case-control clinical trial reported that the HOMA-IR level of T2DM decreased by 73% with 500 mg (×3 daily) berberine for 3 months [ 70 ]. Our results showed that berberine remarkably lower fasting blood insulin, improve HOMA-IR, and decrease BMI, which demonstrated the advantages of berberine on improving insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews showed that berberine improved obesity parameters including BMI [ 68 , 69 ]. Meanwhile, a case-control clinical trial reported that the HOMA-IR level of T2DM decreased by 73% with 500 mg (×3 daily) berberine for 3 months [ 70 ]. Our results showed that berberine remarkably lower fasting blood insulin, improve HOMA-IR, and decrease BMI, which demonstrated the advantages of berberine on improving insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of supplements or functional foods to keep plasma cholesterol concentrations under control is growing steadily in European countries [ 1 , 2 , 3 ] Among these products, phytosterols (or plant sterols) have recently gained traction because their cholesterol-lowering efficacy, within the frame of a healthy lifestyle, is acknowledged by authoritative guidelines [ 4 ] and, among others, by the European Food Safety Authority (EFSA) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, 50% have a higher LDL cholesterol than 120 mg/dl, but 50% a lower, which, however, may have already been lowered by a PE product in combination with additional lifestyle measures resulting in LDL cholesterol levels that are not significantly different between users and nonusers. Evidently, the study does not allow any firm conclusions as to the cholesterol-lowering effect of the intake of PE products or further nutraceuticals in the management of dyslipidemia [13], particularly considering that baseline LDL cholesterol levels before applying PE products are not known.…”
Section: Discussionmentioning
confidence: 96%